2007
DOI: 10.1143/jjap.46.1808
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of Defects by Patterning Using Thermal Nanoimprint Lithography

Abstract: There is strong evidence indicating that the particular form used to recast the Einstein equation as a 3 + 1 set of evolution equations has a fundamental impact on the stability properties of numerical evolutions involving black holes and/or neutron stars. Presently, the longest lived evolutions have been obtained using a parametrized hyperbolic system developed by Kidder, Scheel and Teukolsky or a conformal-traceless system introduced by Baumgarte, Shapiro, Shibata and Nakamura. We present a new conformal-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…the radius of gyration of a polymer) [123,214,314]. An incomplete understanding of defect formation is one challenge facing the commercialization of NIL [336]. The pattern fidelity of NIL is affected by many factors, including the choice of mould material, polymer material, the release layer, pattern complexity, and processing conditions [258,[336][337][338][339].…”
Section: Limitations Of Nanoimprint and Replica Moulding Lithographiesmentioning
confidence: 99%
See 1 more Smart Citation
“…the radius of gyration of a polymer) [123,214,314]. An incomplete understanding of defect formation is one challenge facing the commercialization of NIL [336]. The pattern fidelity of NIL is affected by many factors, including the choice of mould material, polymer material, the release layer, pattern complexity, and processing conditions [258,[336][337][338][339].…”
Section: Limitations Of Nanoimprint and Replica Moulding Lithographiesmentioning
confidence: 99%
“…An incomplete understanding of defect formation is one challenge facing the commercialization of NIL [336]. The pattern fidelity of NIL is affected by many factors, including the choice of mould material, polymer material, the release layer, pattern complexity, and processing conditions [258,[336][337][338][339]. The choice of materials will ultimately be decided by the design rules of a particular application and allowable imprinting conditions (temperature, pressure, and etch selectivity).…”
Section: Limitations Of Nanoimprint and Replica Moulding Lithographiesmentioning
confidence: 99%
“…16) Park et al improved defective transfer in thermal nanoimprinting by changing the imprinting temperature and pressure during pressing. 17) In other studies, longitudinal waves of ultrasonic vibrations were applied during the molding process; 18) this assisted the liquefaction of the softened thermoplastic. The formation of a self-assembled monolayer of fluororesin on the surface of a Ni mold has also been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The highest resolution patterning was demonstrated by Willson at the University of Texas, 1) and by Sakai,2) and Liang et al 3) Multiple spinon planarizing materials for lithography have been also reported. [4][5][6] For advanced nanoimprint lithography, [7][8][9][10][11][12][13][14][15][16][17] however, further technical progress is required in resist pattern peeling, generated defects, process throughput, and the manufacture of high-resolution templates. On these issues, we have developed a new hard mask material with methacrylate side groups in siloxane polymer to obtain a wider imprinting margin, higher regional planarization on…”
Section: Introductionmentioning
confidence: 99%